Mayaro, Trinidad, B.W.I. - Della Costa, M. (Y. De Lima and Co. Ltd., Trinidad, 2009)
This is a painting of a bridge over a river leading to two houses among the coconut trees and the blue sea and the green forested hills in the background.
Colour; Coloured; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Mayaro; Dwellings--Trinidad and Tobago; Coasts--Trinidad and Tobago; Beaches--Trinidad and Tobago; Seaside architecture--Trinidad and Tobago; Architecture--Trinidad and Tobago; Bridges--Trinidad and Tobago